Expression of interleukin-10 splicing variants is a positive prognostic feature in relapsed childhood acute lymphoblastic leukemia - Wu, Shuling; Gessner, Reinhard; Taube, Tillmann; von Stackelberg, Arend; Henze, Günter; Seeger, Karl (Journal of clinical oncology, 2005)
Biologic features of hematologic malignancies have prognostic implications and are essential elements in the design of current therapeutic trials. This study aimed to determine the expression of a splicing-derived variant of interleukin (IL) -10 in leukemic cells and its clinical relevance in children with acute lymphoblastic leukemia (ALL) at first relapse. Between January 1997 and December 2001, bone marrow (BM) samples were collected from 98 children with first relapse of ALL at diagnosis. These patients were enrolled in the relapse trial ALL-REZ BFM (ALL-Relapse Berlin-Frankfurt-Munster) 95 and 96. The detection of IL-10 isoforms in leukemic cells of BM samples were performed by conventional reverse transcriptase polymerase chain reaction and by immunoblotting. IL-10 was detected in 93.9% BM samples. In addition to expressing full-length IL-10, a new splicing-derived IL-10 variant (termed IL-10delta3) that lacked the entire exon 3 was identified in leukemic cells. The IL-10delta3 variant was found in 80.4% of BM samples. Most importantly, expression of IL-10delta3 was associated with a significantly better response to chemotherapy (P = .001) and probability of event-free survival (P = .01) at 5 years. These results indicate that splicing-derived IL-10 isoforms may modulate IL-10-mediated biologic effects and therapeutic efficacy in lymphatic disease, and expression of IL-10delta3 is a positive prognostic feature in relapsed childhood ALL.